1309. Imipenem/Cilastatin/Relebactam (I/R) Alone and in Combination against Pseudomonas aeruginosa (PSA) in the In Vitro Pharmacodynamic Model - Chen, Iris H (Open Forum Infect Dis, 2020)
BACKGROUND: I/R, a carbapenem-beta-lactamase inhibitor antibiotic, is active against most imipenem-resistant PSA, including MDR isolates. Combination therapy may enhance activity against MDR pathogens and suppress resistance. This study’s objective was to assess the efficacy of I/R compared with combinations including colistin (CST) or amikacin (AMK) against PSA in an IVPD model. METHODS: Human-simulated concentrations of I/R 500/250 mg every six hours, a total daily dose of CST 360 mg, and AMK 25 mg/kg daily were reproduced alone and in combination against 6 imipenem-non-susceptible PSA with I/R MICs of 1/4 to 8/4 mg/L in an IVPD over 24h. The primary endpoint was the difference in 24h colony forming units (CFU) between each combination regimen and its components alone. The log ratio differences of the area under the CFU curve were also calculated to compare the overall bacterial burden resulting from exposure to I/R alone with those treated by combination regimens. Emergence of resistance was tested at 24h using drug-containing plates at 3xMIC. RESULTS: I/R, CST, and AMK alone produced 24hCFU changes consistent with isolate MICs. One isolate (already I/R non-susceptible) developed I/R resistance, and 4 and 3 developed CST and AMK resistance, respectively. I/R plus CST suppressed all resistance and resulted in synergistic or additive interactions against three of six isolates with 24h CFU reductions ranging from -2.62 to -4.67 log(10)CFU/mL. This combination further reduced overall bacterial burden by 79-81% compared with I/R alone against two I/R-non-susceptible strains. I/R plus AMK also prevented resistance emergence but exhibited indifferent interactions against all isolates at 24h with the combined drugs achieving -0.51 to -3.33 log(10)CFU/mL reductions. Minor overall reductions in bacterial burden were observed relative to I/R alone. CONCLUSION: I/R plus CST resulted in additivity or synergy against three of six PSA and prevented I/R and CST resistance, whereas the addition of AMK only suppressed resistance. The greatest overall reductions in bacterial burden, however, were observed with I/R plus CST against I/R-non-susceptible isolates, supporting targeted use of this combination against this phenotype when alternatives are unavailable. DISCLOSURES: David P. Nicolau, PharmD, Cepheid (Other Financial or Material Support, Consultant, speaker bureau member or has received research support.)Merck & Co., Inc. (Consultant, Grant/Research Support, Speaker’s Bureau)Wockhardt (Grant/Research Support) Joseph L. Kuti, PharmD, Allergan (Speaker’s Bureau)bioMérieux (Research Grant or Support, Other Financial or Material Support, Speaker Honorarium)Melinta (Research Grant or Support)Merck & Co., Inc. (Research Grant or Support)Paratek (Speaker’s Bureau)Summit (Other Financial or Material Support, Research funding (clinical trials))